How is “Being Well-Matched in Social and Economic Status” Possible: A Study on Contemporary Youth’s Marital Choices from the Perspective of Family System Theory - Dan, Yuzhu (International Journal of Social Sciences and Public Administration, 2024)
As society progresses, people’s perspectives gradually evolve. Nowadays, many believe that marriage is primarily a matter between young couples based on love, yet this does not signify the complete eradication of old-fashioned views from people’s consciousness, as they still influence contemporary marital choices. Families, as the fundamental unit of social organization, bear crucial responsibilities such as nurturing children’s growth. The language and behaviors of family members profoundly shape children’s thoughts and beliefs. Adhering to the theoretical frameworks of marital systems and the concept of “being well-matched in social and economic status”, this paper employs literature research and interviews to delve into the prevailing patterns of contemporary youth’s marital choices and various aspects of their post-marital lives. Consequently, regarding the ancient notion of “being well-matched in social and economic status”, this study analyzes the underlying logic and significance of contemporary youth’s marital “compatibility” from a family system perspective, drawing the following conclusions: The concept of “being well-matched in social and economic status” has undergone a certain degree of evolution, and young people are gradually understanding, accepting, and inheriting this ancient concept; furthermore, marital happiness, longevity, and stability are intimately tied to family structure, relationships, and functions within the broader family system.